Genetic analysis of Escherichia coli strains carrying enteropathogenic Escherichia coli (EPEC) markers, isolated from children in Rio de Janeiro city, Brazil - Regua-Mangia,Adriana Hamond (2003)
In the present study, 47 enteropathogenic Escherichia coli strains identified according to serotyping, presence of eae, bfp and EAF sequences, adherence phenotype and ability to induce attaching-effacing lesions were analyzed by pulsed-field gel electrophoresis (PFGE), multilocus enzyme electrophoresis (MLEE), and the presence of LEE genes (eae, espA, espB, tir) as well as the respective alleles. Amplification of LEE genes subtypes revealed 18 different pathotypes. Typing of the eae gene showed that most strains contained nontypable intimin (42%) followed by beta (35%), gamma and alpha genes (12% each). PFGE analysis revealed a variable degree of polymorphism among isolates and, in general, no clear correlation was observed among PFGE profiles and the virulence markers identified. Otherwise, grouping based on MLEE analysis showed a close association between eae allele and clonal cluster distribution leading us to indicate the eae profile as a promising marker to establish relatedness among such microorganisms.